Power Flow Analysis for the Steel Industry - P.B., Harsha Varthini; K., Yasoda (Journal of Electronics and Informatics, 2025)
Significant equipment like electric arc furnaces (EAFs) and ladle refining furnaces (LRFs) are among the highly dynamic and nonlinear electrical loads found in steel production facilities like Surana Industry. Reactive power imbalance, harmonic distortion, and voltage instability are just a few of the significant power quality issues caused by these complex loads. Because of this, accurate modeling and thorough analysis of these complex power systems are essential to ensuring operational dependability and maintaining power quality. The current literature tends to emphasize mostly steady-state conditions that are frequently not verified empirically with respect to actual operating data, despite the fact that the Electrical Transient Analyzer Program (ETAP) is a common tool used for load flow analysis in industry applications. With an emphasis on accurately simulating the real system behavior under various operating regimes, this paper provides a thorough power flow analysis of the Surana Steel Industry using ETAP. Two 100 MVA, 220/110 kV transformers step down the 110 kV supply that powers the plant, which is drawn from the Chikkasagur substation. The primary loads—a 35-ton rolling mill, a 4 MW EAF, and an LRF are supplemented with a captive power generation system and a harmonic filter to improve power quality and reliability. Under five different operating conditions with different load levels and generator configurations, key performance metrics such as voltage regulation, reactive power flow, harmonic suppression, and generator dynamic response are thoroughly assessed. The power system of the Surana Steel Industry is accurately simulated by the analytical method employed here. Even though a real-time comparison with SCADA data was not attempted, the ETAP model was painstakingly built with detailed equipment specs, typical operating conditions, and performance patterns actually observed at the facility. Accurate simulation of industrial environments, including the complex, unbalanced, and nonlinear loads present in steel mills, was made possible by this all-encompassing approach. Thus, this study shows that when appropriately configured and backed by extensive empirical data, ETAP has a considerable ability to accurately model these difficult environments. These results offer practical information that can be used right away for large-scale industrial power system planning, assessment, and enhancement.
Keywords: Surana Industry; Steel Industry; High Voltage; Transformers; Load; Rolling Mill; Electric Arc Furnace; Ladle Refining Furnace; Harmonic Filter; Generation; Efficiency; Scenarios; ETAP